PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MENGGUNAKAN ADOBE FLASH PADA MATERI DINAMIKA ROTASI DAN KESEIMBANGAN BENDA TEGAR - Rachmawati Rachmawati; M. Rahmad M. Rahmad; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The materials learning physics in class XI senior high school is related to one of the topics on rotational dynamics and rigid-body balance which in fact still has obstacles. One of the problems is the limitations of the media and the lack of interest of students so that the material is generally difficult for students to understand. The use of media in the learning process can increase students' interest in learning, so it is expected to encourage a better learning process. This research aims to develop valid interactive learning media on rotational dynamics and rigid-body balance material using adobe flash applications. The type of research used is R&D (Research and Development). The development model in this research is the ADDIE Model. The learning media developed was validated by 3 experts in their fields as validators. The data analysis used is descriptive analysis, namely by calculating the average of each indicator used to determine the validity of the developed learning media. The results of media validation obtained very high categories so that media were obtained that were already valid. Thus the interactive learning media that has been developed using adobe flash on rotational dynamics and rigid-body balance material, is suitable for use as learning media in class XI senior high school.Key Words: Interactive Learning Media, Adobe Flash, Rotational Dynamics, Rigid-Body Balance